Intramedullary magnetically actuated limb lengthening in a patient with congenital humeral limb shortening. Issue 7 (July 2016) - Tiefenboeck, Thomas M.; Zak, Lukas; Wozasek, Gerald E.
Abstract: The treatment of leg length discrepancy has become a common procedure in orthopaedic surgery. However, lengthening of humeral deformities is still infrequent. The purpose of this case report was to present humeral lengthening with a new intramedullary lengthening device (PRECICE® P2 for tibia) in a 32 year old female patient with congenital shortening. Hereby the telescopic device presents a promising tool for humeral limb lengthening with excellent outcome at short-term in this case.